Philosophy of Action - O'Brien, Lilian. author. aut Link
XV, 172 p.
Keywords: Accessible and wide-ranging, this introduction to contemporary Philosophy of Action guides the reader through the major views and arguments. The topics addressed include the nature of intentional action and its explanation, the nature of reasons, the role of desire and intention in action, the nature of autonomy and the possibility of group agents.